(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The stock market plays a key role in the economy, being one of the main tools for attracting investments and financing companies. Investment activity in the stock market has a significant impact on the financial stability and growth of the country’s economy as a whole. In this article, we will look at the factors influencing investment activity in the stock market, as well as ways to increase it.